Pengaruh Pembangunan Insfrastruktur Terhadap Pertumbuhan Ekonomi di Provinsi Bengkulu - Suyadi, Herman; Nugroho, Sigit; Hutapia, Hutapia (Jurnal Administrasi Bisnis Nusantara, 2026)
The purpose of this research is to analyze the effect of infrastructure development such as road length, electrical energy, Clean and Comsumable and celluler towers on economic growth. Panel data regresion is used to analyze the secondary data, from cities/ districts in the Province of Bengkulu from 2016-2020. The results of the research show that several factors having positive and significant effect on economic growth. those variables are road length, electrical energy, and Clean and Comsumable, while the cellular tower variable has a negative influence but still has a significant effect on economic growth.